Mycobacterium tuberculosis Detection in Diverse Clinical Specimens by GeneXpert MTB/RIF: A Large-Scale Retrospective Study - Li H; Li Z; Cui X; Liu X; Zhao J; Zhang Y; Wang C; Li B; Fan Y; Han J; Xia Y; Xiong Z; et al. (Infection and Drug Resistance)
Haibo Li,1,2,* Ziyao Li,1– 4,* Xiaojing Cui,1,2 Xinmeng Liu,1,2,5 Jiankang Zhao,1,2 Yulin Zhang,1,2 Chunlei Wang,1,2 Binbin Li,1,2 Yanyan Fan,1,2 Jiajing Han,1,2,5 Yudi Xia,1,2 Zhujia Xiong,1,2 Xiaohui Zou,1,2 Yue Zhu,1,2 Mengxue Li,1,2,5 Binghuai Lu,1– 3,5 Bin Cao1– 7 1Laboratory of Clinical Microbiology and Infectious Diseases, Department of Pulmonary and Critical Care Medicine, Center of Respiratory Medicine, National Clinical Research Center for Respiratory Diseases, National Center for Respiratory Medicine, New Cornerstone Science Laboratory, China-Japan Friendship Hospital, Beijing, People’s Republic of China; 2National Center for Respiratory Medicine; State Key Laboratory of Respiratory Health and Multimorbidity; National Clinical Research Center for Respiratory Diseases; Institute of Respiratory Medicine, Chinese Academy of Medical Sciences; Department of Pulmonary and Critical Care Medicine, Center of Respiratory Medicine, China-Japan Friendship Hospital, Beijing, People’s Republic of China; 3Peking Union Medical College, Chinese Academy of Medical Sciences, Beijing, People’s Republic of China; 4Changping Laboratory, Beijing, People’s Republic of China; 5China-Japan Friendship School of Clinical Medicine, Peking University, Beijing, People’s Republic of China; 6Tsinghua University-Peking University Joint Center for Life Sciences, Tsinghua University, Beijing, People’s Republic of China; 7Department of Respiratory Medicine, Capital Medical University, Beijing, People’s Republic of China*These authors contributed equally to this workCorrespondence: Binghuai Lu; Bin Cao, Laboratory of Clinical Microbiology and Infectious Diseases, Department of Pulmonary and Critical Care Medicine, China-Japan Friendship Hospital, No. 2 East Yinghua Street, Chaoyang District, Beijing, 100029, People’s Republic of China, Tel/Fax +86-010-84206256, Email zs25041@126.com; caobin_ben@163.comPurpose: Mycobacterium tuberculosis (MTB) infection poses a significant global health challenge, with conventional diagnostic methods like acid-fast smear and culture techniques exhibiting limitations in sensitivity and efficiency. This retrospective study examined 4098 clinical samples from China-Japan Friendship Hospital between March 2018 and March 2019, focusing on the diagnostic performance of GeneXpert MTB/RIF across different specimen types.Methods: The study encompassed various sample types, including bronchoalveolar lavage fluid (BALF), sputum, lung tissues, hydrothorax, and others. All samples were performed via acid-fast-straining, GeneXpert MTB/RIF and culture.Results: GeneXpert MTB/RIF demonstrated superior sensitivity (81.46%) and specificity (98.98%) in respiratory specimens compared to tissues (62.50%) and hydrothorax (46.15%). Notably, in acid-fast-straining-negative samples, GeneXpert MTB/RIF showed sensitivity and specificity of 73.43% and 98.8%, respectively, and reduced false negatives of acid-fast staining. Furthermore, the study explored Cycler Threshold (CT) values, revealing associations with bacterial load and sample types.Conclusion: The findings highlight the importance of considering sample types in MTB diagnosis and underscore the potential of GeneXpert MTB/RIF as a valuable diagnostic tool, especially in respiratory specimens, contributing to improved tuberculosis management strategies. Additionally, the study recommended direct GeneXpert MTB/RIF testing of hydrothorax samples instead of acid-fast staining, further enhancing diagnostic accuracy and efficiency.Keywords: acid-fast staining, threshold cycle, diagnosis, GeneXpert MTB/RIF, Mycobacterium tuberculosis, tuberculosis